APPLICATION INFORMATION AND LOCATION IN INDONESIA USING VOLCANO VISUAL FOXPRO 9.0 - Heri Iskandar; Yudi Irawan Chandra (Jurnal Sistem Informasi, 2010)
Volcano or volcanoes in general is a term that can be defined as a warm fluidchannel system (the liquid hard core or lava) that extends from a depth of about10 km below the surface of the earth to the upper surface of the earth, includingresult in the the accumulation of material released at the time of eruption.Volcanoes are found in some form throughout their lifetime. Such as activevolcanoes, half of the active or resting.